Comment on: "Comparison of Female Athlete Triad Coalition and RED-S risk assessment tools" - Holtzman, B.; Ackerman, K. (Journal of Sports Sciences, 2020)
Kommentar zur Publikation Koltun, K. J., Strock, N. C. A., Southmayd, E. A., Oneglia A. P., Williams N. I., & De Souza M. J. (2019). Comparison of female athlete triad coalition and RED-S risk assessment tools. Journal of Sports Sciences 37 (21), 2433-2442. [published Online First: 2019/7/13]. https://doi.org/10.1080/2640414.2019.1640551